Linkages between women's empowerment, religion, marriage type, and uptake of antenatal care visits in 13 West African countries. - Michael Nnachebe Onah; Roseline Chinwe Onah; Felix Ezema Onah (Public Library of Science (PLoS), 2023)
Characteristics which reflect a particular context and unique to individuals, households, and societies have been suggested to have an impact on the association between women's empowerment and women's well-being indicators. However, there is limited empirical evidence of this effect. We used access to antenatal care (ANC) to examine the main and interaction effects of women's empowerment, religion, marriage type, and uptake of services in 13 West African countries. Data was extracted from Phase 6 and 7 of the Demographic and Health Survey, and we measured women's empowerment using the survey-based women's empowerment (SWPER) index for women's empowerment in Africa. ANC visits as the outcome variable was analyzed as a count variable and the SWPER domains, religion, and marriage type were the key independent variables. We utilised ordinary least square (OLS) and Poisson regression models where appropriate to examine main and interaction effects and analyses were appropriately weighted and key control variables were applied. Statistical significance was established at 95% confidence interval. Findings suggest that being Muslim or in a polygynous household was consistently associated with disempowerment in social independence, attitude toward violence, and decision-making for women. Although less consistent, improved social independence and decision-making for women were associated with the probability of increased ANC visits. Polygyny and Islamic religion were negatively associated with increased number of ANC visits. Decision-making for Muslim women appear to increase the probability of increased number of ANC visits. Improving the conditions that contribute towards women's disempowerment especially for Muslim women and to a lesser extent for those who reside in polygynous households is key towards better uptake of antenatal care services. Furthermore, targeting of interventions and polices that could empower women towards better access to health services should be tailored on existing contextual factors including religion and marriage type.